Platelet profile of patients with gestational diabetes - Khan, Javid Ahmed; Ashraf, Aadil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Aim was to evaluate the differences in platelet count and platelet indices between pregnant women with gestational diabetes mellitus (GDM) and apparently healthy pregnant women. Methods: A cross-sectional study was performed with 68 pregnant women with GDM (cases) and 68 apparently healthy pregnant women (controls) after 24 weeks of gestation. The study groups were compared in terms of demographic, clinical and laboratory characteristics including platelet count and platelet indices. Results: Mean platelet volume (MPV) (p=0.002*) and platelet distribution width (PDW) (p=0.010*) were significantly increased in pregnant women with GDM compared to the apparent healthy pregnant women (p<0.05). MPV was well correlated with PDW (p=0.00). Conclusions: The platelet indices on CBC testing can aid in identification of GDM, and can help to prevent various complications associated with GDM. The clinical relevance of these platelet indices needs further studies.